The Effectiveness of Schema Therapy training on Personal Values in female with obesity - Ebrahimi, Mansoureh; Raeisi, Zohre; Taheri, Mahdi; Haghayegh, Seyyed Abbas (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to investigate the effectiveness of schema therapy training on personal values of obese women in Tehran in 1399. Method: The research method is quasi-experimental with pre-test-post-test design with control and follow-up groups. The statistical population of the study consisted of all obese women referred to the nutrition and diet therapy clinic in Tehran, from which 40 people were selected by purposive sampling method and randomly in an experimental group (20 people in each group) and one The control group (20 people) was assigned. The experimental group underwent 12 sessions of 60 minutes and the control group remained on the waiting list. The instruments used in the present study included the Personal Values Questionnaire (Schwartz, 2004). Analysis of information obtained from the questionnaire was performed in two parts: descriptive and inferential (analysis of variance with repeated measures). Results: The results showed that schema therapy training has an effect on the components of personal values (power value, progress, hedonism, provocation, self-direction, universality, benevolence, tradition, compliance and security) of obese women (P <0.05). The results showed the effectiveness of schema therapy training on personal values in obese women. Conclusion: Therefore, therapists can use this method to promote mental health in women with obesity.